Analisis Kualitas BOD (Biological Oxygen Demand) dan COD (Chemical Oxygen Demand) Air Sungai Dhurbugan Batuputih Sumenep - Nurul Inayah (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2022)
Abstract River is a natural resource that has a major contribution to human life. Utilization of river water in daily life activities can cause a decrease in water quality. Water quality that is lower than the standard categorized as pollution that causes health risks. River water quality can be carried out by using BOD (Biological Oxygen Demand) and COD (Chemical Oxygen Demand) test parameters. The results of calculating the water quality of the Dhurbugen River obtained a BOD value of 6.448 mg/l and a COD value of 57.6 mg/l. The results of this study concluded that the water quality of the Sumenep Dhurbugan River included in the safe category for water parameters that are in class III and IV based on its utilization function.